Poverty Policy Planning Through Field Condition Mapping: (Study on Community Poverty in Lamongan Regency, East Java Province, Indonesia) - Kurniawan, Andy (Journal of Industrial Engineering & Management Research, 2022)
Poverty handling requires proper planning so that the implementation process runs according to the expected goals. Poverty Planning in Lamongan Regency begins with the step of identifying and mapping the causes of poverty. Special efforts to accelerate poverty reduction in 2021 will be carried out in 6 priority areas with high poverty levels. These efforts are carried out through collaborative interventions, one of which is by mapping poverty reduction programs/activities both sourced from the APBN and from the APBD. Based on this mapping, various programs from both the central and regional governments can be directed to the poor